Kinerja Pegawai Sekertariat (KPU) Kota Ambon dalam Penyelenggaraan Pilkada Tahun 2024 - Indah Kristiani Telaumbanua; Zainal Abidin Rengifurwarin; Iriane Sosiawaty Ponto (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This research is a qualitative descriptive study aimed at understanding and analyzing the performance of the Secretariat employees at the Ambon City General Election Commission (KPU) in 2024. The study was conducted at the Ambon City KPU. The data collection techniques used were observation, interviews, and documentation with a total of 10 informants who were considered directly involved in the role of the Secretariat employees’ performance in organizing the local election. The results of this study indicate that the performance of administrative services is not yet optimal or has not been implemented properly. This can be seen from the research findings regarding service standards, which include several indicators: service procedures, completion time, facilities and infrastructure, and the competence of service officers. The study concludes that improvements are needed in discipline, knowledge, skills, and expertise of the officers so that the service process can be carried out effectively.